2017
DOI: 10.1096/fj.201600976r
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mitochondrial activity in colonocytes facilitates AMPKα2‐dependent inflammation

Abstract: Intestinal inflammation is associated with low levels of mucosal ATP, highlighting the importance of mitochondrial function associated with ATP production in the pathophysiology of the disease. In the inflamed colon of humans and mice, we found decreased levels of mitochondrial complex cytochrome oxidase I/IV and lower ATP levels. Thus, we generated colonic ρ cells with reduced mitochondrial function linked to ATP production by selective depletion of mitochondrial DNA. In these cells, RNA sequencing revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 62 publications
0
36
0
Order By: Relevance
“…Mice treated with dextran sodium sulfate (DSS) to induce colitis exhibited swollen mitochondria, increased mtROS generation, decreased ETC activity and ATP level in the colonic mucosa that was ameliorated by anti-TNFα treatment. 54,64 Mice with deletion of IRGM, a CD susceptibility gene that affects mitochondrial fission and induces autophagy, exhibited increased susceptibility to experimental colitis. 65,66 Polymorphisms in SLC22A5, which encodes OCTN2 the carnitine transporter involved in mitochondrial FAO, are associated with CD risk.…”
Section: Mitochondrial Dysfunction and Inflammatory Bowel Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice treated with dextran sodium sulfate (DSS) to induce colitis exhibited swollen mitochondria, increased mtROS generation, decreased ETC activity and ATP level in the colonic mucosa that was ameliorated by anti-TNFα treatment. 54,64 Mice with deletion of IRGM, a CD susceptibility gene that affects mitochondrial fission and induces autophagy, exhibited increased susceptibility to experimental colitis. 65,66 Polymorphisms in SLC22A5, which encodes OCTN2 the carnitine transporter involved in mitochondrial FAO, are associated with CD risk.…”
Section: Mitochondrial Dysfunction and Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…54,77 Infliximab, an anti-TNFα biologic therapy for IBD, was shown to be beneficial to reduce mitochondrial dysfunction in cultured IECs and IBD patients. 54,78 The role of microbiome in mitochondrial alterations driving epithelial barrier dysfunction will be discussed in the following section.…”
Section: Mitochondrial Dysfunction and Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…For example, alteration in expression of established MSI “driver” genes, such as MutL Homolog 1 (MLH1), did not meet the statistical threshold and thus was not a part of ρ 0 DE transcripts used for analysis. Also, as emerging findings show that mitochondria function could impact inflammation and nuclear DNA replication [ 21 , 26 , 28 ], we speculate, that in colonic ρ0 cells DE associated with MSI phenotype could be the consequence of both inflammation and aberrant DNA replication. Moreover, it is important to consider the colonic ρ 0 transcriptome might also be driven by parental HCT116 cell mutations in K-ras and β-catenin genes (KRAS, CNNTB1) [ 29 ], Thus we performed unsupervised hierarchical clustering of activated canonical pathways from ρ 0 transcriptomes with parental HCT116 cells and colon cancer RKO cells with wild-type K-ras and β-catenin.…”
Section: Resultsmentioning
confidence: 70%
“…We found that decreased ATP synthase subunit ATP5A1, the enzyme responsible for catalyzing ATP production, is linked with considerably reduced colon cancer patient survival (Fig 1A ) (p < 0.05). Since this supports a critical role for reduced mitochondrial energy function in colon cancer pathobiology, we analyzed in colonic ρ0 cells with decreased mitochondrial ATP production [ 21 ] if differentially expressed (DE) transcripts were associated with human colon cancer. Utilizing Ingenuity Pathway Analysis (IPA), we found that these DE transcripts were linked with cancer and cellular functions associated with cell cycle, proliferation, DNA replication and repair, cellular movement, cell survival, and tumor morphology (Fig 1B ) (FDR < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation